2020
DOI: 10.1002/jhbp.790
|View full text |Cite
|
Sign up to set email alerts
|

Gram staining of gallbladder bile samples is useful for predicting surgical site infection in acute cholecystitis patients undergoing an early cholecystectomy

Abstract: Acute cholecystitis (AC) is one of the most frequently encountered diagnoses in the emergency room, with its prevalence increasing worldwide. 1-3 The recommended treatment is an early cholecystectomy, which ought to be performed close to the time of the disease onset. 1 A common complication after cholecystectomy for AC is surgical site infection (SSI); its rate has been reported to be almost 10 percent. 4 For the prevention and control of such infection, multimodal strategies and multidisciplinary efforts are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The perprotocol analysis revealed a significantly higher rate of organ or space infections in the no-prophylaxis group. Multivariable analysis showed that omitting antibiotic prophylaxis and a positive bile culture were associated with surgical-site infections, in line with previous studies 22,23 .…”
Section: Discussionsupporting
confidence: 89%
“…The perprotocol analysis revealed a significantly higher rate of organ or space infections in the no-prophylaxis group. Multivariable analysis showed that omitting antibiotic prophylaxis and a positive bile culture were associated with surgical-site infections, in line with previous studies 22,23 .…”
Section: Discussionsupporting
confidence: 89%
“…This high morbidity rate is partly due to SSIs, which are reported to occur in 10% of cholecystectomies. [7][8][9] The high incidence of SSIs is suspected due to pathogen contamination of the bile fluid in the surgical incision and organ space. Positive culture bile culture correlate with an increased risk of postoperative infection.…”
mentioning
confidence: 99%